ON SERIES OF GENERATORS SYSTEMS FOR AUTOMATON PERMUTATION GROUPS - Sikora, Vira (Sworld-Us Conference proceedings, 2025)
The article investigates the construction of generators systems for automaton permutation groups that act on the set of all words over a given alphabet or on the set of words of length () over this alphabet. It is established that the group induced by aut